2018
DOI: 10.1186/s12884-018-2001-0
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of simulation-based shoulder dystocia training- impact on obstetric outcome, clinical management, staff confidence, and the pedagogical practice - a time series study

Abstract: BackgroundTo assess the impact of 10 years of simulation-based shoulder dystocia training on clinical outcomes, staff confidence, management, and to scrutinize the characteristics of the pedagogical practice of the simulation training.MethodsIn 2008, a simulation-based team-training program (PROBE) was introduced at a medium sized delivery unit in Linköping, Sweden. Data concerning maternal characteristics, management, and obstetric outcomes was compared between three groups; prePROBE (before PROBE was introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 25 publications
2
61
0
1
Order By: Relevance
“…The results of this study [13] revealed that implementing the shoulder dystocia training program led to a significant decrease in injuries related to delivery.…”
Section: Theoretical Frameworkmentioning
confidence: 72%
See 2 more Smart Citations
“…The results of this study [13] revealed that implementing the shoulder dystocia training program led to a significant decrease in injuries related to delivery.…”
Section: Theoretical Frameworkmentioning
confidence: 72%
“…Dahlberg, Nelson, Dahlgren, & Blomberg [13] conducted a study in Sweden in which a simulation-based training program was introduced on a labor and delivery unit. "Data concerning maternal characteristics, management, and obstetric outcomes was compared between three groups" [13].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in Obstetrics teaching, the use of simulators and simulation environments has been studied in various settings (8) , mostly obstetric emergencies such as shoulder dystocia (11)(12) , postpartum hemorrhage (13)(14)(15)(16)(17)(18) , pre-eclampsia and eclampsia (16)(17) . There is also evidence on simulation to enhance surgical skills such as suturing of vaginal and severe lacerations (19) .…”
Section: Givenmentioning
confidence: 99%
“…A 2014 literature review showed that after simulations, it was possible to observe an increase in knowledge as well as technical, communication and teamwork skills (16) . A 10-year followup study of a simulation-based training for shoulder dystocia management identified an increasing in the number of diagnosis and a decreasing in the number of neonatal brachial plexus lesions (11) . At least one study conducted in Mexico (1) was able to demonstrate that the implementation of a continuing education program including simulations has successfully modified obstetric practice with better results in terms of good practices adoption.…”
Section: Givenmentioning
confidence: 99%